Tradisi Politik Melayu : Analisis Sistem Marga Uluan Dan Iliran Di Sumatera Selatan - Niko Oktario Adytyas; M Sirajudin Fikri (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2022)
The writing in this study aims to unravel the existence of traditional political system in modern era, besides wanting to investigate more about how dichotomized between uluan and Iliran society. The method used in this research uses qualitative research method with primary and secondary data sources sought by interview data collection techniques, observation and documentation techniques and then in analysis with the researchers' need for data presented in this study. In this study can be drawn some conclusions, the dichotomy between Uluan and Iliran is based on the understanding of each society towards their culture, at a later stage affecting their daily lives hereditary. Second, the declining custom is applied in the Uluan and Iliran communities in dominnation with the traditional system of government with the implementation of traditional authorities in the succession of leadership, where the head of government is elected hereditary. The next stage in the dynamics of the traditional system of government does not strip away the State and Religion, therefore there needs to be an appropriate middle way to accommodate all interests. There must be a mutually filling nature between the two, namely the opportunity for religion to fill the ethical dimension of state life and religious morality, so that the formulation of "The State of Indonesia is not a religious state nor a secular state", but a country in which the values of religions can live and exist .